MARINE DEBRIS AT INDRAMAYU TOURISM BEACH, WEST JAVA: DENSITY AND COMPOSITION - Adzhari , Natasya Syafa; Hidayati, Nuning Vita; Hendrayana, Hendrayana; Andriyono, Sapto (Jurnal Perikanan Unram, 2025)
Marine debris is a solid material that is intentionally or unintentionally left in the waters and can directly threaten the condition and productivity of water areas. Tirta Ayu Beach and Balongan Beach are tourist destinations that are threatened by marine debris. The presence of tourists on the beach is very beneficial for increasing regional and community income, but it can also result in an increase in the generation of waste generated so that a lot of this waste accumulates and is distributed to various places and has a negative impact on the waters. This study aims to determine the species composition, weight, density, and distribution of marine debris at Tirta Ayu Beach and Balongan Beach. Sampling was conducted at 8 research stations, then classified and analyzed based on UNEP and KLHK provisions. The results showed that the types of marine debris found on Tirta Ayu Beach and Balongan Beach included plastic, plastic foam, rubber, paper and cardboard, wood, glass, cloth, and other materials. Plastic is a type of marine debris dominating Balongan Beach (89%) and Tirta Ayu Beach (81%). The highest density value of marine debris based on quantity and weight was found on Tirta Ayu Beach with a value of (5.0 ± 1.9 items/m2) and a weight of 25.8 ± 16.3 gram/m2.